ASUHAN KEPERAWATAN PADA BY.NY M DENGAN PENERAPAN POSISI QUARTER PRONE PADA PASIEN RDS (RESPIRATORY DISTRESS SYNDROM) DALAM MENJAGA KESTABILITAS RESPIRATORY RATE DAN SATURASI OKSIGEN DI RUANGAN NICU RSBP BATAM - Halimatusyakdiah, Nur; Febrina, Trisya Yona; Fatrida, Dedy (Ensiklopedia of Journal, 2025)
Abstract: Respiratory Distress Syndrome is a neonatal morbidity that often occurs throughout the world, the prevalence of RDS reported from several countries is 18.5% in France, 4.24% in Pakistan and 20.5% in China, in Indonesia the cause of considerable mortality in the neonatal period in 2022 conditions of Low Birth Weight (LBW) (28.2%) and Asphyxia by (25.3%). and babies admitted to the Neonatal Intensive Care Unit (NICU) at the time of the study were 5 babies and on average with diagnoses of RDS, LBW and Hypoglycemia. and babies admitted to the Neonatal Intensive Care Unit (NICU) room at the time of the study were 5 babies and on average with diagnoses of RDS, LBW and Hypoglycemia. After carrying out nursing care, it is hoped that the author can apply nursing care comprehensively and according to nursing care standards with the application of the Quarter prone position in RDS (Respiratory Distress Syndrom) patients in maintaining the stability of Respiratory Rate and Oxygen Saturation Application of Quarter prone position in RDS (Respiratory Distress Syndrom) patients in maintaining the stability of Respiratory Rate and Oxygen Saturation in the NICU Room. This research is descriptive research with a case study approach. And the results of this study showed an increase in Respiratory Rate and oxygen saturation (SpO2), as well as a decreased pulse rate, decreased shortness of breath, improved breathing frequency and decreased use of breathing muscles. The quarter prone position is very influential for training breathing and cardiovascular and this position is recommended to stabilize Respiratory rate and oxygen saturation.Keywords: Respiratory Distress Syndrome, Quarter Prone position, Respiratory Rate, Oxygen Saturation